Oh my God, where does your maths teacher, no all your maths teachers since junior high, plus those in Chemistry, Physics and Computer science come from? Adeptus Inumeratus?

(x-5\sqrt(x)-24)^2=x^2-25x-24^2-2x5\sqrt(x)-2x24+2*5\sqrt(x)24. The rest you can do yourself, I hope.

You can't simply put square on each term of the sum - (1+1+1)^2=9 but 1^2+1^2+1^2=3! The general formula is as follows:

(a_1+a_2+....a_n)^2= a_1^2+a_2^2+....a_n^2+2a_1a_2+2a_1a_3+...2a_{n-1}a_n

You take all squares and add to them twice the product of every two terms!